PENERAPAN MODEL PEMBELAJARAN TIPE JIGSAW TERHADAP MOTIVASI DAN HASIL BELAJAR KIMIA PADA MATERI HIDROKARBON SISWA KELAS X SMA KRISTEN WAMENA - Malino, Indrawati (Jurnal Ilmu Pendidikan Indonesia, 2013)
This research aim to look at: (1) the differences of study motivation between students in class that process learning use type Jigsaw and student in class that use type STAD, (2) the differences study result of hydrocarbon between students in class that process learning use type Jigsaw and student in class that use type STAD, (3) increase of study resulton class control and class experiment. The population in the research were students on class X SMA Kristeb Wamena, total 108 students, and sample were (1) students on class XC as expreriment class that process learning used type Jigsaw, (2) students on class XB as control that used type STAD. Design of research was Pretest â Posttest Control Group Design. The technique of data analysis used the different test (t-test) with software SPSS 16. The result showed that: (1) there was difference of study motivation between syudents on class that process learning used type Jigsaw and on class XB as control that used type STAD with significance score t 0,01 < 0,05, (2) there was difference result stuidy between students on class that process learning used type Jigsaw and on class XB as cobtrol that used type STAD with significance score t 0,000 < 0,05 (3) there was increase of chemistry result study on class experiment and class control. Keywords : Jigsaw, STAD, Motivation, Result Study, Hydrocarbon